2017
DOI: 10.1007/s00228-017-2308-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for unintentional medication reconciliation discrepancies in preadmission medication: a systematic review

Abstract: Multiple suitable predictors for PAM-related discrepancies were identified of which higher age and polypharmacy were reported most frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 52 publications
7
34
2
5
Order By: Relevance
“…Besides, our results were close to those of another study. Hias et al revealed that polypharmacy was a factor that explained the increased risk of discrepancies on patient admission. Finally, by providing exhaustive data on the medication supply over the past 4 months, the ePR prevents the risk of forgetting a practitioner prescription.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, our results were close to those of another study. Hias et al revealed that polypharmacy was a factor that explained the increased risk of discrepancies on patient admission. Finally, by providing exhaustive data on the medication supply over the past 4 months, the ePR prevents the risk of forgetting a practitioner prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Trinh‐Duc et al reported in their study (on an emergency unit) that the ePR was the only source of information available for 25% of the cases . The ePR could also be useful for other populations, especially to meet the challenge of MedRec for elderly patients on multiple drugs, particular features predictive of the occurrence of unintentional discrepancies …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations